AtATM Is Essential for Meiosis and the Somatic Response to DNA Damage in Plants - Garcia, Valérie (American Society of Plant Biologists, 2003)
In contrast to yeast or mammalian cells, little is known about the signaling responses to DNA damage in plants. We previously characterized AtATM, an Arabidopsis homolog of the human ATM gene, which is mutated in ataxia telangiectasia, a chromosome instability disorder. The Atm protein is a protein kinase whose activity is induced by DNA damage, particularly DNA double-strand breaks. The phosphorylation targets of Atm include proteins involved in DNA repair, cell cycle control, and apoptosis. Here, we describe the isolation and functional characterization of two Arabidopsis mutants carrying a T-DNA insertion in AtATM. Arabidopsis atm mutants are hypersensitive to γ-radiation and methylmethane sulfonate but not to UV-B light. In correlation with the radiation sensitivity, atm mutants failed to induce the transcription of genes involved in the repair and/or detection of DNA breaks upon irradiation. In addition, atm mutants are partially sterile, and we show that this effect is attributable to abundant chromosomal fragmentation during meiosis. Interestingly, the transcription of DNA recombination genes during meiosis was not dependent on AtATM, and meiotic recombination occurred at the same rate as in wild-type plants, raising questions about the function of AtAtm during meiosis in plants. Our results demonstrate that AtATM plays a central role in the response to both stress-induced and developmentally programmed DNA damage.